2017
DOI: 10.1038/leu.2017.9
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of the CTLA-4 ligand CD86 on plasmacytoid dendritic cells (pDC) predicts risk of disease recurrence after treatment discontinuation in CML

Abstract: It is unknown, why only a minority of chronic myeloid leukemia (CML) patients sustains treatment free remission (TFR) after discontinuation of tyrosine kinase inhibitor (TKI) therapy in deep molecular remission (MR). Here we studied, whether expression of the T-cell inhibitory receptor (CTLA-4)-ligand CD86 (B7.2) on plasmacytoid dendritic cells (pDC) affects relapse risk after TKI cessation. CML patients in MR displayed significantly higher CD86pDC frequencies than normal donors (P<0.0024), whereas TFR patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 53 publications
0
72
1
Order By: Relevance
“…Some studies have recently indicated that an increased proportion of mature natural killer cells and expression of the cytotoxic T-lymphocyteassociated protein 4 (CTLA-4) ligand CD86 on plasmacytoid dendritic cells are associated with the risk of relapse after TKI discontinuation. Therefore, immunologic factors may be linked with molecular relapse-free survival, [30][31][32] as also suggested by the higher rates of successful TFR associated with prior treatment with recombinant interferon, an immunomodulatory agent. 20 In this context, the differences in transcript immunogenicity may help to explain the differences observed in TFR in the current study between subgroups with the e13a2 and e14a2 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have recently indicated that an increased proportion of mature natural killer cells and expression of the cytotoxic T-lymphocyteassociated protein 4 (CTLA-4) ligand CD86 on plasmacytoid dendritic cells are associated with the risk of relapse after TKI discontinuation. Therefore, immunologic factors may be linked with molecular relapse-free survival, [30][31][32] as also suggested by the higher rates of successful TFR associated with prior treatment with recombinant interferon, an immunomodulatory agent. 20 In this context, the differences in transcript immunogenicity may help to explain the differences observed in TFR in the current study between subgroups with the e13a2 and e14a2 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TNF-α/IFN-γ cytokine secretion by these activated CD56 dim CD16 − NK cells correlated with TFR success (18). A separate sub-study of 122 EURO-SKI patients has recently reported that increased CD86 + pDCs, which mediate immune tolerance are found in MolR patients at the time of TKI cessation, and thus low CD86 + pDC might be predictive of TFR (19). This study also found that higher numbers of pDCs correlated with increased PD-1-expression on PR3-specific CD8 + CTLs, suggesting immune exhaustion contributes to relapse risk.…”
Section: Role Of the Immune System For Successful Tfrmentioning
confidence: 99%
“…Very recently, an increased proportion of mature, adaptive-like CD56 dim NK cells have been observed in CML patients who successfully discontinued imatinib (18). Other immunologic mediators such as plasmacytoid dendritic cells (pDCs), which may serve as promising prognostic factors for successful TFR, are also currently under investigation (19). TKIs also exert significant off-target multikinase inhibitory effects, albeit with differing potencies.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological biomarkers at the time of TKI discontinuation are linked to the likelihood of continuous TFR, including increased natural killer (NK) cells [10,11] and CD86-positive plasmacytoid dendritic cells (pDC) [12] numbers and function, the latter being also linked to a T cell exhaustion phenotype with high PD-1 expression potentially also at least in part explaining limited anti-leukemic potency of leukemia antigen(LAA)-specific cytotoxic T lymphocytes. The latter study also suggested that the number of CD86-positive pDC overrules the time effect of previous therapy on TFR likelihood, as in patients with high CD86 pDC numbers (>95/µl) the effect of previous TKI therapy duration does not at all impact TFR rates, whereas in patients with low CD86 pDC numbers, long-term TKI pretreated patients have a 90% success rate of being continuously TKI free.…”
Section: Which Biomarkers Predict Successful Treatmentfree Remission?mentioning
confidence: 99%